Supervisi Akademik Kepala Madrasah Dalam Meningkatkan Pembelajaran Kelompok Pendidikan Agama Islam Di MAN 1 Lampung Selatan - Yazid, Mamnoni (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2021)
The principal has a great duty and responsibility, namely the principal to foster and guide teachers to form the character of quality human students. The research method used is descriptive qualitative. The results obtained: 1) The efforts of the head of madrasa in choosing strategies and directing learning to adjust the curriculum and kbm during the pandemic, briefings are also carried out in meetings so that the implementation does not encounter obstacles. 2) In the implementation of learning uses such as google meet, google zoom and e-learning also make it easier for educators, the efforts made by madrasa heads such as workshops, technical guidance and other training with the aim of improving competence also run smoothly. 3) The importance of motivation for madrasah principals makes teachers more aware of managing learning facilities, especially in learning more using digital technology. 4) The Head of Madrasah always provides motivation and guidance on the use of technology, the results and what is achieved cannot be separated from the teacher's contribution in providing learning delivery as well as academic and non-academic achievements that have been achieved.